2019
DOI: 10.1093/jnen/nlz120
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FOXP3 in Canine Gliomas: Immunohistochemical Study of Tumor-Infiltrating Regulatory Lymphocytes

Abstract: Dogs develop gliomas with similar histopathological features to human gliomas and share with them the limited success of current therapeutic regimens such as surgery and radiation. The tumor microenvironment in gliomas is influenced by immune cell infiltrates. The present study aims to immunohistochemically characterize the tumor-infiltrating lymphocyte (TIL) population of naturally occurring canine gliomas, focusing on the expression of Forkhead box P3-positive (FOXP3+) regulatory T-cells (Tregs). Forty-three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 58 publications
2
20
2
Order By: Relevance
“…This study is the largest and most comprehensive characterization of inflammatory infiltrates in canine glioma to date, adding to the few previous studies in the dog. 1,18,55,63 In this study, we found robust infiltration of Iba1þ microglia and macrophages into gliomas, with smaller numbers of CD3þ and CD20þ lymphocytes. FoxP3þ cells were found in all cases but were more numerous in high-grade tumors.…”
Section: Discussionsupporting
confidence: 59%
“…This study is the largest and most comprehensive characterization of inflammatory infiltrates in canine glioma to date, adding to the few previous studies in the dog. 1,18,55,63 In this study, we found robust infiltration of Iba1þ microglia and macrophages into gliomas, with smaller numbers of CD3þ and CD20þ lymphocytes. FoxP3þ cells were found in all cases but were more numerous in high-grade tumors.…”
Section: Discussionsupporting
confidence: 59%
“…35,36 Prior studies have demonstrated elevated numbers of CD4+ Foxp3+ regulatory T cells intratumorally and in the peripheral blood of dogs with gliomas, as well as an increased proportion of plasmacytoid dendritic cells. 29,37 In humans, the IDO pathway has been shown to play an important role in plasmacytoid dendritic cell-induced Foxp3+ regulatory T-cell differentiation. 38 Forthcoming immunohistochemical analyses of our tumor specimens will allow us to validate the importance of IDO expression in canine gliomas.…”
Section: Figmentioning
confidence: 99%
“…The expression level of three immune checkpoint molecules was determined by the percentage of positive cells and the staining intensity: low (negative intensity and intensity 1, and intensity 2 with positive cells < 10%) and high (intensity 2 with positive cells ≥ 10% and intensity 3) expression (19). The expression of TILs/TAMs was similarly evaluated as previously described (20,21).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%